Human Resources Monitoring System using Sensors GPS on Android Smartphone - Karjadi, Daniel (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Smartphone technology is currently developing rapidly. In an effort to improve and empower companies, smart is used as a tool for anything in office work and in projects. For example, smartphones are currently used for meetings or coordination with leaders and employees. In the project, smartphones can be used to monitor employees. One of the problems with work on projects is that employees often leave project work for several reasons. The position of employees is often unknown to other employees or leaders. So the idea arose to find out the whereabouts of the employee. Monitoring employees on the project is very important, where the presence of these employees is needed to coordinate. If the employee is at risk of a work accident, the management quickly knows the position of the employee. The idea of ​​making employee monitoring in the project by creating an application system for employee positions in the project. In addition to monitoring, employees do not need to attend the office, from the employee's home directly to the project site and do asben from the project site. The data will record the name of the employee, the position of the employee in the project, the time of absence, see the tasks that will be carried out per day. The results of the task are carried out by taking selfies as a report to superiors. The purpose of this research is to solve the problem of the existence of employees or the position of employees in the project, to be absent at the project site, to take selfies on the progress of daily work, and to hold meetings with the application. This application is built using technology based on the Android system using Flutter.